APROPRIASI MUSIK KELOMPOK REBANA KASUKA NADA - Kuwat; Nuuriyah Tarjono, Siti; Yanuar, Dani (Institut Seni Indonesia (ISI) Surakarta, 2024)
This research discusses the reasons related to the thoughts of the Kasuka Nada tambourine group in choosing musical appropriation in their performances. Tambourines are mostly dominated by percussion instruments such as flying, but now tambourine music has experienced developments in innovation in terms of music media and song repertoire using adaptations of songs popularized by other singers, and adapting other people's works. This form of tambourine music innovation is called appropriation. The purpose of this study is to describe the process of appropriating music in the Kasuka Nada tambourine group, to describe the factors that influence the Kasuka Nada tambourine group in appropriating, to analyze the musical results of the Kasuka Nada tambourine group's musical appropriation, and to describe how the Kasuka Nada tambourine group performs. . This research was conducted using a qualitative descriptive analysis method, by way of describing the existing facts and then proceed with the analysis. The method used in this study is divided into four stages, namely data collection, data processing, data analysis, and drawing conclusions. The theoretical basis used to dissect this research is the theory of appropriation and performance theory. Based on the data analysis conducted, it was concluded that the purpose of the tambourine group appropriating is to preserve and maintain the continuity of tambourine music. Presenting trending songs and those that are liked by the public and then changing the lyrics to the theme of goodness and commendable teachings which are inserted with prayers are the hallmarks of the Kasuka Nada tambourine group, and there are internal and external factors that influence the Kasuka Nada tambourine group in appropriation of music.